(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Culture is a tool that speaks about the nation's past, present and future, and introduces it to the world. In this article, the attention paid to the field of culture and art in Uzbekistan, the measures being implemented and planned to be implemented in the future, are discussed. spoken.